Farmer Experimenters : Self-Developed Technology - Bunch, Roland; Canas, Mateo (World Bank, Washington, DC, 2012)
The note examines the experience of self-developed technologies by farmer experimenters (FEs) in Honduras, based on a study by the Association of Advisors for a Sustainable, Ecological, and People-Centered Agriculture - COSECHA - and shows how FEs are capable of developing large numbers of significant, and original technologies, providing evidence that the collecting, and dissemination of FEs technologies in other nations, could be useful for institutions involved in agricultural development. The note further explores the participatory technology development, the results to date of the technologies discovered, and those promising technologies to be developed.